A New Four‐Arm Organosiloxane with Thermopolymerizable Trifluorovinyl ether Groups: Synthesis and Conversion to the Polymer with both Low Dielectric Constant and Low Water Uptake. Issue 13 (26th April 2017) - Xin, Yumeng; Wang, Jiajia; Jin, Kaikai; Luo, Yijie; Zhou, Junfeng; Wang, Yuanqiang; Sun, Jing; Zheng, Shijun; Fang, Qiang
Abstract : A new fluoro‐containing polysiloxane showing low dielectric constant, low water uptake, high transparency, and high thermostability is successfully synthesized by direct thermocrosslinking of a four‐arm organosiloxane having thermopolymerizable trifluorovinyl ether groups. Abstract : A new fluoro‐containing four‐arm organosiloxane has been successfully synthesized, which can be easily converted to a cross‐linked network, showing water uptake of below 0.12 wt% (maintained in boiling water for 72 h) and dielectric constant of below 2.56 with dissipation factor of near 1.8 × 10 −3 at 30 MHz, as well as showing high transparency and good thermostability. These data indicate that this new organosiloxane is suitable as an adhesive or sealant for the applications in microelectronic industry.